Evaluation of the antitumor effect of Calotropis procera (Aiton) Dryand (Apocynaceae) in vitro and in vivo - Rabêlo, Ana Carolina Silveira (2020)
Cancer is the main public health problem worldwide and although advances have been made in anticancer therapy, there are still many gaps. In this sense, our goal was to evaluate the antitumor effect of Calotropis procera, a plant popularly used to treat several diseases, especially related to gastric and inflammatory disorders. For this, we divided the thesis into three chapters. First, it was demonstrated a general review of the main phytochemicals and biological effects described for this plant. In the second chapter, it was carried out the characterization of the crude ethanolic extract of C. procera leaves (CE), where mainly flavonoids, glycosides and cardenolides were found. We also evaluated the antitumor effect of CE, methanolic (MF) and ethyl acetate (EAF) fractions of C. procera in canine mammary tumor (CMT) and canine osteosarcoma (OST) cells. As a positive control, it was used the chemotherapy drug-doxorubicin. Results demonstrated that C. procera treatment reduced the cell viability and proliferation of CMT and OST, reflecting the cell arrest in the G0/G1 phase. C. procera also altered the morphology of tumor cells, making them more round and smaller, which is suggestive of apoptosis. In fact, through flow cytometry analysis, we found that C. procera increased caspase-3, reduced angiogenesis and the mesenchymal epithelial transition, and increased p53 in OST cells; in addition to reducing PCNA in CMT cells. Finally, in the third chapter, the antimetastatic effect of crude extract phenolics from C. procera (CphE) was evaluated in 4T1 breast cancer cells and in mammary tumors of nude mice xenograft model. Quercetin - a flavonoids present in C. procera - was used as positive control. The in vitro results demonstrated that CphE reduced 4T1 cells viability and the levels of ROS, induced apoptosis, modulated Akt/mTOR, MAPK pathways, reduced cell migration, and epithelial-mesenchymal transition. In vivo, CphE reduced ERK1/2 in breast tumors, and reduced liver and lung metastasis, by reducing Cenpf and Twist. All of these results analyzed together strongly suggest that C. procera has great potential as an antitumor agent.